Prehospital Supraglottic Airways: An NAEMSP Position Statement and Resource Document. (4th January 2022) - Lyng, John W.; Baldino, Kimberly T.; Braude, Darren; Fritz, Christie; March, Juan A.; Peterson, Timothy D.; Yee, Allen
Abstract: Supraglottic airway (SGA) devices provide effective conduits for oxygenation and ventilation and may offer protection from gastric aspiration. SGA devices are widely used by EMS clinicians as both rescue and primary airway management devices. While in common use for more than four decades, major developments in SGA education, science, and technology have influenced clinical strategies of SGA insertion and use in prehospital airway management for patients of all ages. NAEMSP recommends: SGAs have utility as a primary or secondary EMS airway intervention. EMS agencies should select SGA strategies that best suit available resources and local clinician skillset, as well as the nature of their clinical practice setting. EMS agencies that perform endotracheal intubation must also equip their clinicians with SGA devices and ensure adequate training and competence. In select situations, drug-assisted airway management may be used by properly credentialed EMS clinicians to facilitate SGA insertion. Confirmation of initial and continuous SGA placement using waveform capnography is strongly encouraged as a best practice. When it is functioning properly, EMS clinicians should refrain from converting an SGA to an endotracheal tube. The decision to convert an SGA to an endotracheal tube must consider the patient's condition, the effectiveness of SGA ventilations, and the clinical context and course of initial SGA insertion SGA training, competency, and clinical use must be continuously evaluated by EMS agencies using focused quality management programs.